Does the blood glucose control have an effect on the success of the painful diabetic neuropathy treatment? - Jovanikić Olivera; Anđelić Gordana; Lepić Milan; Mirković Dušica; Jovanović Bojan; Lepić Toplica; Dragović Tamara (Vojnosanitetski Pregled)
Background/Aim. Diabetic neuropathy (DN) is the basic complication of diabetes, associated with impared glucoregulation, metabolic distrurbances, microvascular vessel damage and increased cardiovascular risk. We monitored the impact of glucoregulation on the efficacy of painful diabetic neuropathy (PDN) treatment, when all pharmaceutical treatment options were exhausted. Methods. Patients (n = 53, both gender, average age 68.3 ± 12.6) with PDN resistant to the pharmacotherapy were treated with the ultrasound- guided local anesthetic (0.5% procaine hydrochloride, 1% lidocaine, 0.25% levobupivacaine) blocks. Neuropathy was confirmed in accordance with the applicable European Federation of Neurological Societies (EFNS) criteria. Glycosylated hemoglobin (HbA1C) and blood glucose levels were monitored before and after therapy and one month after the treatment. Neuropathic pain was confirmed by Leeds Assessment of Neuropathic Symptoms and Signs (LANSS) or Douleur neuropathique (DN4) or pain DETECT scales. The pain intensity was assessed by Visual analog scale, Neuropathic pain symptom and Neuropathic pain symptom inventory (VAS, NPS and NPSI, respectively) scales before and after therapy and one month after the treatment. The efficacy of the therapy was assessed as: excellent result (> 50% of pain loss), good result (30%–49% of pain loss and the therapy does not work (< 30% of pain loss). The correlation between glucoregulation and the outcome was examined. Results. Because the values of glycenia and HbA1c were not different among patients treated with different local anesthetics, they were presented together. All patients had elevated blood glucose and HbA1C levels before (8.23 ± 2.77 mmol/L and 8.53% ± 2.48% respectively), after (8.43 ± 2.461 mmol/L and 8.85% ± 2.87%, respectively) and one month after the treatment (8.49 ± 2.22 mmol/L and 8.51% ± 2.09%, respectively). The loss of the pain was not result of the decrease in blood glucose and HbA1C blood levels. VAS, NPS, NPSI values were the following before the therapy: 81.53 ± 11.62 mm; 62.00 ± 13.04; 53.40 ± 17.63, respectively; after the therapy: 29.00 ± 9.23 mm; 13.79 ± 6.65; 11.83 ± 7.93, respectively; and one month later: 26.15 ± 8.41 mm; 12.68 ± 6.03; 9.81 ± 7.64, respectively]. There was no correlation between glucoregulation and excellent outcome. Conclusion. Even though the disturbance of glucose control is the key factor for the progression of PDN, it is not significant for the outcome of the pain treatment. New investigations are required.